Contributions of the Food Acquisition Program to the strengthening of family farming, food and nutritional security: an integrative review - da Silva, Vanessa Cristina [UNESP]; Barim, Estela Maria [UNESP]; Murta-Nascimento, Cristiane [UNESP] (FapUNIFESP (SciELO), 2025)
Established in 2003 as part of the Zero Hunger Program, the Food Purchase Program (PAA) is a crucial structural public policy to combat hunger and strengthen family farming. The program has suffered systematic budgetary and operational dismantling, concomitantly with Brazil’s rise in food insecurity. This integrative literature review examines the significance of PAA in ensuring food sovereignty and empowering family farming. The literature search was conducted in December 2022, encompassing Portuguese, Spanish, and English publications within a ten-year timeframe. The databases used were SciELO and BVS, which include LILACS and MEDLINE. Thirty-five publications were identified, and eight articles were included in this review after analysis. The documented experiences demonstrate the effectiveness of the PAA in combating hunger and contributing to the promotion of food security in rural families. Nevertheless, the program faces challenges related to budget cuts, the discontinuation of operational modalities and the lack of structure as a State policy. In light of this, there is an urgent need to revise the PAA's organizational structures and consolidate this program as a critical state policy, not only to ensure its resistance but also to regain its effectiveness.
Contribuições do Programa de Aquisição de Alimentos para o fortalecimento da agricultura familiar e segurança alimentar e nutricional: revisão integrativa
Keywords: Food Acquisition Program; Food and nutritional security; Public Policy; Sustainable Agriculture